Responsabilidad social universitaria y formación profesional de los psicólogos peruanos - Arias Gallegos, Walter (2025)
In this article, the links between university social responsibility and the professional training of psychologists in Peru are critically reviewed. For this, the current situation of the academicprofessional aspects related to university education in the country is first reviewed, specifically in the psychology career. Then, relevant aspects of corporate social responsibility are explained, leading to university social responsibility, and its implications in the training of Peruvian psychologists. Finally, some conclusions on the points discussed are presented.